2021
DOI: 10.1002/ab.21994
|View full text |Cite
|
Sign up to set email alerts
|

Sex differences of parental phubbing on online hostility among adolescents: A moderated mediation model

Abstract: To explore the relationship between parental phubbing (PP) and adolescent online hostility and its' psychological mechanism, 689 Chinese adolescents were recruited to complete a paper-and-pencil questionnaire. We took cyber flaming (CF) as an overall category for hostile online communication to investigate the relationship between PP and CF and the mediating role of perspective-taking (PT) in this relationship and examined whether there is a sex difference in this process. After controlling the average daily o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 62 publications
0
3
0
Order By: Relevance
“…However, in a study by X. Wang, Wang, et al (2020), the gender variable did not appear explain the relationship between parental phubbing and cyberbullying. In another study, H. Wang et al (2022) found that although parental phubbing was positively related to cyberbullying in both genders, a moderating effect of the perspective adopted in this relationship existed only for boys.…”
Section: Gender and Age Differences And Family Variablesmentioning
confidence: 96%
“…However, in a study by X. Wang, Wang, et al (2020), the gender variable did not appear explain the relationship between parental phubbing and cyberbullying. In another study, H. Wang et al (2022) found that although parental phubbing was positively related to cyberbullying in both genders, a moderating effect of the perspective adopted in this relationship existed only for boys.…”
Section: Gender and Age Differences And Family Variablesmentioning
confidence: 96%
“…Among the mentioned research, supervisor phubbing is proven to have a different influential path on their subordinates in individual psychological conditions [17,24], emotions and attitudes [1,9,19,23], and working performance [9,18,25]. What is noteworthy is that phubbing can result in stressful conditions for the neglected person [23,24,26,27]. Flagged as a typical counterproductive workplace managerial behavior [19,24], supervisor phubbing is proven to negatively impact subordinates' psychological conditions, such as producing withdrawal tendencies [6], lower employees' organizationbased self-esteem [19], engagement level, identification, and trust in their supervisor [17].…”
Section: Introductionmentioning
confidence: 99%
“…However, these technologies can sometimes disrupt or impair parent–child interactions (Mcdaniel & Coyne, 2016). The phenomenon that parents are distracted or ignore their children because of their smartphones when they are interacting with their children is defined as parental phubbing, which is a negative form of parent–child interaction and has attracted the interest of researchers (Wang, Gao, et al, 2020; Wang, Zhou, et al, 2022). As a new form of social exclusion (David & Roberts, 2017), parental phubbing negatively impacts adolescents’ psychological development, such as reducing the quality of parent–child communication, impairing adolescents’ interpersonal communication ability, and increasing the risk of accidental injury and problem behaviors (for a review, see Jiang et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Despite the growing body of research linking parental phubbing to adolescent problem behavior, these studies have mainly focused on online behavior, such as cyberbullying and Internet addiction (Geng et al, 2021; Wang & Lei, 2022; Wang, Wang, et al, 2022; Wang, Zhou, et al, 2022; Wei et al, 2021; Zhang, Ding, et al, 2021). Limited research has studied the relationship between parental phubbing and adolescent offline behaviors, particularly general aggression (Wang, Qiao, et al, 2022).…”
Section: Introductionmentioning
confidence: 99%